2016
DOI: 10.1016/j.drugalcdep.2016.09.024
|View full text |Cite
|
Sign up to set email alerts
|

The effects of a repeated dose of a recombinant humanized anti-cocaine monoclonal antibody on cocaine self-administration in rats

Abstract: Background Immunotherapy has shown potential as a treatment for cocaine abuse. The humanized recombinant anti-cocaine monoclonal antibody (mAb) with the preclinical designation h2E2 has been shown to decrease cocaine concentrations in the brain in rats, but its effects on cocaine self-administration behavior have never been tested. Methods The amount of cocaine needed to reinstate self-administration behavior (priming threshold) was calculated and the inter-injection intervals at unit doses of 0.3 μmol/kg an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 29 publications
(40 reference statements)
1
17
0
Order By: Relevance
“…As potential immunotherapeutics for the treatment of cocaine abuse, the murine-derived chimeric mAb GNC92H2 (Carrera et al, 2005), the humanized mAb h2E2 (Norman et al, 2014) and the fully human anti-cocaine mAb GNCgzk (Treweek & Janda, 2012) have been generated and characterized with regard to their affinities and specificities for cocaine and its metabolites. Additionally, in rodent models the in vivo ability of anti-cocaine mAbs to (i) decrease brain cocaine concentrations by restricting its distribution from plasma, (ii) increase the drug levels needed to reinstate cocaine-dependent self-administration behavior in trained rats and (iii) substantially reduce cocaine toxicity/lethality have been well documented (Treweek & Janda, 2012;Norman et al, 2007Norman et al, , 2009Norman & Ball, 2012;Wetzel et al, 2016). Based on such preliminary studies, the mAb h2E2 is entering phase 1 clinical trials for cocaine abuse therapy.…”
Section: Introductionmentioning
confidence: 99%
“…As potential immunotherapeutics for the treatment of cocaine abuse, the murine-derived chimeric mAb GNC92H2 (Carrera et al, 2005), the humanized mAb h2E2 (Norman et al, 2014) and the fully human anti-cocaine mAb GNCgzk (Treweek & Janda, 2012) have been generated and characterized with regard to their affinities and specificities for cocaine and its metabolites. Additionally, in rodent models the in vivo ability of anti-cocaine mAbs to (i) decrease brain cocaine concentrations by restricting its distribution from plasma, (ii) increase the drug levels needed to reinstate cocaine-dependent self-administration behavior in trained rats and (iii) substantially reduce cocaine toxicity/lethality have been well documented (Treweek & Janda, 2012;Norman et al, 2007Norman et al, , 2009Norman & Ball, 2012;Wetzel et al, 2016). Based on such preliminary studies, the mAb h2E2 is entering phase 1 clinical trials for cocaine abuse therapy.…”
Section: Introductionmentioning
confidence: 99%
“…It has a long half-life in both rats and mice [5,7]. This mAb also increased the amount of cocaine needed to reinstate self-administration behavior in a rat model of relapse by 3-fold [8], which should translate into a decrease in the probability of cocaine induced relapse. On the basis of these findings h2E2 is a lead candidate as an immunotherapeutic for cocaine abuse.…”
Section: Introductionmentioning
confidence: 99%
“…The mAb h2E2 has high affinity and selectivity for cocaine over its inactive metabolites [4,5] and has a long plasma half-life in both rats and mice. In rats, the recombinant humanized mAb has been shown to decrease brain concentrations of cocaine [4] and prevent cocaine-induced priming of self-administration behavior [6]. In mice, h2E2 can antagonize the distribution of cocaine's active metabolite, cocaethylene, into the brain [7].…”
Section: Introductionmentioning
confidence: 99%
“…However, many of these assumptions have been called into question. For example, it is speculated that high selectivity of the humanized anti-cocaine mAb h2E2 over the major inactive metabolite benzoylecgonine may not be ideal, and may exacerbate the increase in cocaine consumption that is observed after the mAb has been surmounted [6]. Extensive study of anti-methamphetamine mAbs with varying pharmacological profiles has also revealed that in vitro affinities and in vivo pharmacokinetic half-life are not always predictive of the magnitude and duration of action of these antibodies [8].…”
Section: Introductionmentioning
confidence: 99%